LITERATURE REVIEW: ANALYSIS OF GREEN SUPPLY CHAIN MANAGEMENT (GSCM) - Muhammad Hilman Fikri; Solawati Nainggolan; Julianto Hutasuhut (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
Generally, in the current era of globalization, distribution and logistics have played an important role in the growth and development of world trade. Moreover, increasingly fierce business competition requires companies to restructure their business strategies and tactics, especially in terms of distribution and logistics. The essence of competition lies in how a company can implement the processes of creating products or services that are cheaper, have a better quality, and are faster to obtain (cheaper, better and faster) than business competitors